Dynamic hydrogen bonding and DNA flexibility in minor groove binders: molecular dynamics simulation of the polyamide f‐ImPyIm bound to the Mlu1 (MCB) sequence 5′‐ACGCGT‐3′ in 2:1 motif. Issue 5 (24th February 2015) - Bruce, Chrystal D.; Ferrara, Maddi M.; Manka, Julie L.; Davis, Zachary S.; Register, Janna
<x xml:space="preserve">Abstract</x> Molecular dynamics simulations of the DNA 10‐mer 5′‐CCACGCGTGG‐3′ alone and complexed with the formamido‐imidazole‐pyrrole‐imidazole (f‐ImPyIm) polyamide minor groove binder in a 2:1 fashion were conducted for 50 ns using the pbsc0 parameters within the AMBER 12 software package. The change in DNA structure upon binding of f‐ImPyIm was evaluated via minor groove width and depth, base pair parameters of Slide, Twist, Roll, Stretch, Stagger, Opening, Propeller, and x‐displacement, dihedral angle distributions of ζ, ε, α, and γ determined using the Curves+ software program, and hydrogen bond formation. The dynamic hydrogen bonding between the f‐ImPyIm and its cognate DNA sequence was compared to the static image used to predict sequence recognition by polyamide minor groove binders. Many of the predicted hydrogen bonds were present in less than 50% of the simulation; however, persistent hydrogen bonds between G5/15 and the formamido group of f‐ImPyIm were observed. It was determined that the DNA is wider in the Complex than without the polyamide binder; however, there is flexibility in this particular sequence, even in the presence of the f‐ImPyIm as evidenced by the range of minor groove widths the DNA exhibits and the dynamics of the hydrogen bonding that binds the two f‐ImPyIm ions to the minor groove. The Complex consisting of the DNA and the 2 f‐ImPyIm binders shows slight fraying of the 5′ end of the 10‐mer at the end of the simulation, but the portion of the oligomer responsible for recognition and binding is stable throughout the simulation. Several structural changes in the Complex indicate that minor groove binders may have a more active role in inhibiting transcription than just preventing binding of important transcription factors. Copyright © 2015 John Wiley & Sons, Ltd.